2022
DOI: 10.1021/acs.jpcc.1c10226
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Energy Hotspot: Effects of Impact Velocity, Defect Geometry, and Crystallographic Orientation

Abstract: In energetic materials, the localization of energy into “hotspots” is known to dictate the initiation of chemical reactions and detonation. Recent all-atom simulations have shown that more energy is localized as internal potential energy (PE) than can be inferred from the kinetic energy (KE) alone. The mechanisms associated with pore collapse and hotspot formation are known to depend on pore geometry and dynamic material response such as plasticity. Therefore, we use molecular dynamics (MD) simulations to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 79 publications
2
23
0
Order By: Relevance
“…These hotspots originate entirely from inter-granular pore collapse as no defects are built within the grains during the building process. A comparison of this temperature map with the initial microstructure, Figure 6(a), indicates that elongated pores result in the highest temperatures, this is consistent with prior MD simulations [11,40].…”
Section: Tatb-ps: Shock Loadingsupporting
confidence: 87%
See 1 more Smart Citation
“…These hotspots originate entirely from inter-granular pore collapse as no defects are built within the grains during the building process. A comparison of this temperature map with the initial microstructure, Figure 6(a), indicates that elongated pores result in the highest temperatures, this is consistent with prior MD simulations [11,40].…”
Section: Tatb-ps: Shock Loadingsupporting
confidence: 87%
“…The shock compression of materials can drive a variety of events such as phase transformations [1][2][3], plasticity [4][5][6][7], melting [8,9], intra-molecular deformations [10][11][12], and chemical reactions [13][14][15][16]. Most of these phenomena can be exacerbated by the localization of energy due to the interaction of the shockwaves with the materials microstructure and defects.…”
Section: Introductionmentioning
confidence: 99%
“…Recent MD simulations revealed that the shock-induced collapse of porosity results not just in energy localization in the form of heating but also in significant intramolecular strains 42,43 . The excess potential energy (PE), or intramolecular strain energy 44 , is readily stored in modes relevant to prompt chemical initiation and exceeds the expected value based on the thermal vibrational energy 42 .…”
mentioning
confidence: 99%
“…Here, we aim to utilize all-atom molecular dynamics to study the entire extemporaneous event via the shock initiation of a porous sample of TATB (1,3,5-triamino-2,4,6-trinitrobenzene), an insensitive HE material. Our simulation setup is designed with inspiration from previous studies ,, to provide the best opportunity to see an extemporaneous mechanochemical event.…”
mentioning
confidence: 99%
See 1 more Smart Citation